Development of My Toy House Online Ordering System for My Toy House Online Store - Tai, Sing Yong; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2021)
For the present generation where almost everyone has a smartphone with them, online shopping has become a trend, as more peoples prefer to purchase products online. In order to cope with it, an e-commerce system which is My Toy House Online Ordering System has been decided to be developed for My Toy House Online Store. A traditional way of recording which is a manual filing system is currently used by the store owner and this has slowed down the product managing process. Other than that, delay of communication is also one of the problem faced. Extra charges for each transaction carried out is also a problem faced by the store owner. The system is developed by using object-oriented approach and the information required is gathered by using two data gathering method which is interview and observation. The system offers services such as stock management and online selling products. For management, the system shall allow the user to manage the stock information such as quantity, price and name while for online business, the system shall allow the user to view the products details, manage account and search product. With the implementation of the system, the usage of the paper can be reduced as record is kept using the system. Other than that, the system allows easy management and increase the interest of the client as it does not require extra charges for each transaction.